2022
DOI: 10.3390/photonics9030174
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Way of Phase Synchronization of a Self-Injected Bunch and an Accelerating Wakefield in Solid-State Plasma

Abstract: The electron acceleration, in a laser wakefield accelerator, controlled through plasma density inhomogeneity is studied on a basis of 2.5-dimensional particle-in-cell simulation. The acceleration requires a concordance of the density scale length and shift of the accelerated electron bunch relative to wake bubble during electron acceleration. This paper considers the excitation of a wakefield in plasma with a density equal to the density of free electrons in metals, solid-state plasma (the original idea of Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(25 reference statements)
2
2
0
Order By: Relevance
“…Comparing the results of the current study with previous studies [27,28], it can be concluded that the current study provides the process of formation and subsequent retention of a self-injected bunch at laser amplitudes 2.0 [27] and 3.33 [28] times smaller, which brings the research topics closer to experimental realization. In the current study, a 10 4 times lower plasma density is considered.…”
Section: Fig 3 Plasma Electron Density and Longitudinal Electric Fiel...supporting
confidence: 71%
See 2 more Smart Citations
“…Comparing the results of the current study with previous studies [27,28], it can be concluded that the current study provides the process of formation and subsequent retention of a self-injected bunch at laser amplitudes 2.0 [27] and 3.33 [28] times smaller, which brings the research topics closer to experimental realization. In the current study, a 10 4 times lower plasma density is considered.…”
Section: Fig 3 Plasma Electron Density and Longitudinal Electric Fiel...supporting
confidence: 71%
“…In addition, in the current study, compared to [27,28] an increase in the bunch charge from 0.56 to 20 pC (by a factor of 35.7) is observed. Also, an energy increase of 7.67 times compared to 3.67 times [28] for the observed time intervals is observed.…”
Section: Fig 7 Plasma Electron Density and Longitudinal Electric Fiel...supporting
confidence: 49%
See 1 more Smart Citation
“…Synchronization of self-injected bunches with an accelerating field in a metal-density plasma was also studied [13,14].…”
Section: Introductionmentioning
confidence: 99%